تحسين أداء الشبكات اللاسلكية عن طريق اختيار المعيار الأمثل لعملها - عائشة جمعة (Tishreen University, 2019)
WLAN networks have attracted the attention of many researchers in the field of communications and information technology because of the advantages of this type of network and its wide spread in various scientific and applied fields. The researchers proposed many Improvments to the work of these networks in order to develop them and overcome the difficulties Which suffer from it, which earns them greater durability and reliability. These networks are capable of data transfer according to several standards developed by the IEEE. These standards differ from one another according to several factors including data transfer rate, authentication methods and other features that have been developed and improved the performance of these networks as a whole . In this study we simulated the WLAN operating according to the IEEE 802.11b and IEEE 802.11 g standards by proposing a set of scenarios involving different numbers of nodes in each scenario and then comparing the performance of these two parameters according to a set of basic parameters that evaluate network performance Such as throughput, load and time delay, in order to assess both the performance of the two standards and to identify the best scenarios for their work respectively. تحظى شبكات الـ WLAN باهتمام العديد من الباحثين في مجالات الاتصالات وتكنولوجيا المعلومات، نظراً للميزات التي تتمتع بها مثل هذا النوع من الشبكات، وانتشارها الواسع في مختلف المجالات العلمية والتطبيقية، حيث عمد الباحثون إلى اقتراح العديد من التعديلات على عمل هذه الشبكات بهدف تطويرها والتغلب على الصعوبات التي تعاني منها، مما يكسبها متانة وموثوقية أعلى. تتميز هذه الشبكات بقدرتها على نقل البيانات وفق عدة معايير تم تطويرها من قبل المعهد الدولي للهندسة الكهربائية والالكترونية IEEE، وتختلف هذه المعايير عن بعضها البعض وفقاً لعدة عوامل منها معدل نقل البيانات، وطرق المصادقة وغيرها من الميزات التي تم العمل على تطويرها وتحسينها أداء هذه الشبكات ككل. تم في هذا البحث محاكاة شبكة الـ WLAN التي تعمل وفقاً لمعيارين IEEE 802.11 b و المعيار IEEE 802.11 g من خلال اقتراح مجموعة من السيناريوهات المتضمنة على أعداد مختلفة من العقد في كل سيناريو ومن ثم مقارنة أداء هذين المعيارين بحسب مجموعة من البارامترات الأساسية التي تقيم أداء الشبكة مثل المردود والحمل والتأخير الزمني، وذلك بهدف الوصول إلى تقييم أداء كل من المعيارين ومعرفة السيناريوهات الأفضل لعمل كل منهما.